Educação ambiental na educação de jovens e adultos: memórias de estudantes sobre as transformações ambientais - Gouveia, Natalia Lázara (2023)
Youth and Adult Education (EJA) has a long history in Brazilian education, going through several moments of struggle to become effective and ensure the eradication of illiteracy in the country, which still has high numbers. In this context, we sought to uncover the following problem: What is the view of EJA students on the environment and the transformations observed throughout their lives? The aim of this research was to develop a didactic sequence in order to contribute to the environmental education of these students, recovering memories and perceptions about the environmental transformations they have experienced throughout their lives. We used qualitative research, through participant observation and interviews with seven EJA students at the Olintha de Oliveira Vale Municipal School in Araporã-MG. Most of the students started from an understanding of the environment as consisting only of natural elements, without any human intervention. However, over the course of the meetings, the activities carried out made it possible to reflect on these conceptions and gain a better understanding that they, as subjects, transform, are transformed by and make up the environment. During the interview, we identified that among the most striking environmental transformations were the changes in their childhood home, when the houses were made of mud, covered with coconut palm leaves and with dirt floors, to today's houses which are made of cement. There were also reports about the transformations in the municipality of Araporã-MG, its growth in terms of the increase in the number of neighborhoods and houses in the city, where sugar cane used to be planted, and the transformation of a swamp into a lake, which is now a tourist attraction. Around 90% of the students associated the solution to environmental problems with individual and simplistic attitudes, which we tried to change through debates and the drafting of a collective letter to the town hall, with a view to building collective awareness. The didactic strategies adopted in the sequence aroused the students' interest, stimulated participation and contributed to the development of a broader view of the environment in which they live. It is worth noting that this work generated the educational product entitled "Environmental Education in Youth and Adult Education: students' memories of environmental transformations".